The Core Vocabulary: The Foundation of Proficient Comprehension. (19th February 2020) - Hiebert, Elfrieda H.
Abstract: A group of words, labeled the core vocabulary, can be expected to be prominent across all texts. Scholarship made possible by digital databases of words and new analytic systems has shown that approximately 2, 500 morphological families account for most of the words in texts—an average of 91.5% of all words in the Common Core State Standards exemplars from kindergarten through College and Career Ready. The rare vocabulary of texts is so extensive and varied that, without a foundation in the core vocabulary, students are likely to struggle with the meanings of rare words. Words are in the core vocabulary because they represent critical concepts, are part of morphological or word families that share a root word, and are often versatile in their meaning and function. The author describes the semantic, morphological, and multiple‐meaning knowledge represented by these 2, 500 word families and ways in which teachers can foster these proficiencies.